Preface. Palaeodiversity and Palaeoecology of Iberian Ecosystems. New insights into the Phanaerozoic biotas from Spain and Portugal - Furió, M.; Martínez-Pérez, C.; Santos-Cubedo, A. (Journal of Iberian Geology, 2014)
Preface. Palaeodiversity and Palaeoecology of Iberian Ecosystems. New insights into the Phanaerozoic biotas from Spain and Portugal